2014
DOI: 10.5959/eimj.v6i2.238
|View full text |Cite
|
Sign up to set email alerts
|

Preparing nursing students for interprofessional learning

Abstract: Introduction: Teaching strategies for nursing students need to be varied to prepare them for their future practice, and to increase their confidence levels in order to ensure that they deliver high quality care to patients. Interprofessional learning (IPL) is a way to develop health professional teams in that it facilitates collaboration by having health professional students learn with, from and about each other's roles and responsibilities in the provision of patient care. At present, nurses are unable to le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…Findings from the FGD showed that nursing students had positive views towards IPL. One of the student, (Student 4), agreed to be exposed early as this is an exposure in preparing them for the future working environment (11). Thus, this FGD showed that there is suggestion to consider at the year of study on the exposure towards IPL.…”
Section: Focused Group Discussionmentioning
confidence: 88%
“…Findings from the FGD showed that nursing students had positive views towards IPL. One of the student, (Student 4), agreed to be exposed early as this is an exposure in preparing them for the future working environment (11). Thus, this FGD showed that there is suggestion to consider at the year of study on the exposure towards IPL.…”
Section: Focused Group Discussionmentioning
confidence: 88%
“…This is because simulation as a teaching tool is relatively new in Malaysia (Ismail 2015). Whilst the usage of simulation as a teaching tool has gained momentum over the last five to ten years in the global arena (Kneebone et al 2005) and inter-professional training (Karim et al 2014) the awareness of using simulation for research is still lacking. Nevertheless, this is a common finding in many other studies even in countries where the use of simulation is well established (Bradley 2006;McGaghie et al 2010;McGaghie et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Las estrategias de enseñanza interprofesional permitirán a los estudiantes de enfermería prepararlos para el trabajo colaborativo y mejorar su nivel de confianza en la atención directa al paciente (12) , así como empoderarles en su rol de gestión del cuidado. En este sentido, la gestión del cuidado considerando entre otras cosas brindar un cuidado planificado, utilizando los recursos disponibles, fijado objetivos, metas y estrategias y liderar la colaboración entre los equipos de profesionales de la salud (13) .…”
Section: Introductionunclassified